Whistler Instability Driven by Electron Thermal Ring Distribution With Magnetospheric Application. Issue 7 (13th July 2019) - Yoon, P. H.; Lee, Junggi; Hwang, Junga; Seough, J.; Choe, G. S.
Abstract: The loss cone electron distribution function can be unstable to the excitation of whistler instability, which can be effective in pitch angle diffusion, thus rapidly filling up the loss cone and removing the free energy source. The present paper carries out a combined quasi‐linear analysis and one‐dimensional particle‐in‐cell simulation in order to investigate the dynamical consequences of the excitation of whistler instability. Thermal ring distribution can be considered as a simple substitution for the actual loss cone distribution. It is found according to both the reduced quasi‐linear theory and the particle‐in‐cell simulation that while the whistler instability is effective in pitch angle diffusion of the initial loss cone distribution, the complete isotropization is not achieved such that substantial loss cone persists in the saturation stage. This finding may explain the fundamental question of why weak loss cone feature persists in the magnetosphere and, more importantly, why charged particles trapped in dipole field do not steadily undergo pitch angle scattering and be lost eventually. Key Points: Magnetospheric loss cone electrons modeled by thermal ring distribution can be unstable to whistler instability Reduced quasi‐linear theory and PIC simulation show that substantial loss cone persists in the saturation stage The present finding explains why electrons trapped in dipole field do not steadily undergo pitch angle scattering to be lost eventually